Perancangan Produk Outsole Kelom Geulis Berbahan Bambu Dengan Fokus Pada Kebaruan Kreasi - Reza Hamidah; Mohamad Waskito (Penerbit Itenas, 2024)
This research was motivated by sustainability efforts, avoiding the threat of scarcity of the main raw materials for kelom geulis, namely Mahogany and Albasiah wood, and providing novelty and design innovation for kelom geulis footwear. Bamboo is used as a substitute for wood because it has the ability to regenerate faster and has good strength and has the opportunity to develop more varied shapes. Through the utilization of lamination techniques, bamboo is expected to be a novelty that can increase the economic value of kelom, open industrial opportunities, and greater market opportunities. The method used in this research is the material experimentation method, which is a trial method that explores novelty opportunities through printing and lamination techniques to achieve the feasibility of the function and shape of the sole as a footwear component. The target of this research is to produce a prototype kelom geulis with a sole that is unique in terms of shape and visual distinctiveness adopted from the physical properties of bamboo as an alternative raw material using laminated bamboo. The result of this research is a novelty in footwear design that has a new touch that is different from existing kelom geulis products, creating new economic opportunities in the bamboo sector, and efforts to promote the sustainable use of natural resources.